Developing Early Literacy Skills A Meta-Analysis of Alphabet Learning and Instruction - Piasta, Shayne B (Reading research quarterly, 2010)
Alphabet knowledge is a hallmark of early literacy and facilitating its development has become a primary objective of pre-school instruction and intervention. However, little agreement exists about how to promote the development of alphabet knowledge effectively. A meta-analysis of the effects of instruction on alphabet outcomes demonstrated that instructional impacts differed by type of alphabet outcome examined and content of instruction provided. School-based instruction yielded larger effects than home-based instruction; small-group instruction yielded larger effects than individual tutoring programs. We found minimal evidence of transfer of alphabet instruction to early phonological, reading, or spelling skills. Implications for research and practice are discussed